2021
DOI: 10.1186/s40478-021-01304-5
|View full text |Cite
|
Sign up to set email alerts
|

IDH-wild type glioblastomas featuring at least 30% giant cells are characterized by frequent RB1 and NF1 alterations and hypermutation

Abstract: Giant cell glioblastoma (GC-GBM) is a rare variant of IDH-wt GBM histologically characterized by the presence of numerous multinucleated giant cells and molecularly considered a hybrid between IDH-wt and IDH-mutant GBM. The lack of an objective definition, specifying the percentage of giant cells required for this diagnosis, may account for the absence of a definite molecular profile of this variant. This study aimed to clarify the molecular landscape of GC-GBM, exploring the mutations and copy number variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…8 We recently found that, above the high frequency of TP53 mutations, GBMs histologically featuring at least 30% giant cells (GCs) display a significantly higher rate (25.6%) of RB1 alterations than conventional GBMs (9.4%). 5 This finding, also reported by other authors, 9 suggests that the alteration of RB1 could be a further distinctive feature of GBMs with GCs.…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…8 We recently found that, above the high frequency of TP53 mutations, GBMs histologically featuring at least 30% giant cells (GCs) display a significantly higher rate (25.6%) of RB1 alterations than conventional GBMs (9.4%). 5 This finding, also reported by other authors, 9 suggests that the alteration of RB1 could be a further distinctive feature of GBMs with GCs.…”
Section: Introductionsupporting
confidence: 69%
“…5,12 In a subset of cases (42GL-71GL), the results were confirmed using the SureSelectXT HS CD Glasgow Cancer Core assay (Agilent Technologies, Santa Clara, CA, USA). 5 In the remaining five GBMs with GCs and eight PXAs (cases 1X-14X), we used the Oncomine Tumour Mutational Load (TML) panel (Thermo Fisher) to assess the mutations and CNV of 409 cancer-related genes.…”
Section: E T H I C Smentioning
confidence: 82%
See 3 more Smart Citations